In silico and in vivo evaluations of multistage antiplasmodial potency and toxicity profiling of n-Hexadecanoic acid derived from Vernonia amygdalina - Afolayan, F. I. D.; Odeyemi, R. A.; Salaam, R. A. (Frontiers in Pharmacology, 2024)
Background: Despite the widely reported potentials of n-Hexadecanoic acid (HA) as a bioactive, its multi-stage antiplasmodial activity and toxicity profiles remain largely unknown.Methodology: Thus, this study uses a combination of in silico approaches and in vivo studies to assess the inhibitory activities of HA at different stages of the Plasmodium lifecycle, antiplasmodial performance, and toxicity profiles. The HA was retrieved from the PubChem database, while antiplasmodial target proteins from different stages of the Plasmodium falciparum life cycle were collated from the Protein Databank (PDB). Molecular Docking and Visualization were conducted between the compound and target proteins using AutoVina PyRx software and Biovia Discovery Studio, respectively. Also, the AdmetLab 3.0 algorithm was used to predict the absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) profiles of HA. Based on a 4-day suppressive test, the antiplasmodial activity against the Plasmodium berghei ANKA strain in mice was evaluated. Furthermore, subacute toxicity and micronucleus assays were used for further toxicity assessment.The molecular docking analysis indicates multi-stage, multi-target potentials of HA with favourable ligand-receptor complexes across the four Plasmodium falciparum stages.Meanwhile, the mice administered with 100 mg/kg, 50 mg/kg, and 10 mg/kg of HA demonstrated considerable chemosuppression in a dose-dependent manner of 89.74%, 83.80%, and 71.58% percentage chemosuppression, respectively, at p<0.05. The ADMET prediction, histopathological tests, and micronucleus assays show that HA is safer at a lower dose.This study showed that n-Hexadecanoic acid is a potential drug candidate for malaria. Hence, it is recommended for further molecular and biochemical investigations.